Low-concentration methanol effect on the microorganisms, nitrogen removal, and recovery of the completely autotrophic nitrogen removal over nitrite - Xiu Yue; Ao You; Yang Liu; Mincheng Lai; Kun Zhang (Water Science and Technology, 2023)
Methanol has a significant effect on the performance of the completely autotrophic nitrogen removal over the nitrite (CANON) process. In this research, the effect of low-concentration methanol on the functional microorganisms and nitrogen removal and recovery in the CANON system is investigated. The result shows that the anaerobic ammonium-oxidizing bacteria (AnAOB) was suppressed with low-concentration methanol addition, and the phylum Planctomycetes was hidden. The genus Candidatus Brocadia was restrained, and the relative abundances reduced from 25.5 to 15.0% in the upper biofilm and from 20.3 to 14.3% in the bottom biofilm, respectively. However, low-concentration methanol promoted the nitrifying oxidizing bacteria (NOB) activity. This phenomenon reduced the average ammonium nitrogen removal rate from 95.0 to 70.7%, and the average total nitrogen removal rate decreased from 81.3 to 43.6%, respectively. The results demonstrated that the low-concentration methanol as an organic carbon matter harmed the CANON process. Fortunately, the CANON system had an excellent self-healing ability when the methanol was stopped, with the average ammonium nitrogen removal rate and total nitrogen removal rate returning to 95.5 and 80.9%, respectively. This research supplies a reference for practical engineering design and application by improving the understanding of the effects of low-concentration methanol on CANON process performance. HIGHLIGHTS Low-concentration methanol harmed the CANON process in a SABF system.; The relative abundance of anammox bacteria reduced because of a low-concentration methanol.; The genus Candidatus Brocadia was suppressed due to the low-concentration methanol.; The relative abundance of nitrifying bacteria increased with a low-concentration methanol.; The CANON system had an excellent self-healing ability without methanol addition.;